Cervical uterine cancer: prevention and treatment - Eneida Bravo Polanco; Narciso Águila Rodríguez; Dayamí Guerra Villarpanda; Yamiley Blanco Vázquez; Oskeimy Rodríguez González; Madelín Oliva Santana (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Cervical uterine cancer is a cellular alteration which starts in the cervix epithelium due to the persistence of human papillomavirus oncogenic serotypes and that initially manifests itself through precancerous lesions of slow and progressive evolution. It still is the leading cause of morbidity and mortality in women in developing countries. World statistical data indicates that some 466,000 new cases occur each year, 80% of them in developing countries, of which 274,000 women die, despite being a preventable disease. The objective of this review is to compile information on its prevention and treatment, in order to be used for educational purposes.